Avengers. Infinity war [videorecording (Blu-Ray + 4K Ultra HD)] - Silvestri, Alan (Marvel Studios, 2018)
As the Avengers and their allies have continued to protect the world from threats too large for any one hero to handle, a new danger has emerged from the cosmic shadows: Thanos. A despot of intergalactic infamy, his goal is to collect all six Infinity Stones, artifacts of unimaginable power, and use them to inflict his twisted will on all of reality.